Kiss of the spider woman - Puig, Manuel,1932-1990 (Vintage Books, 1991)
Sometimes they talk all night long. In the still darkness of their cell, Molina re-weaves the glittering and fragile stories of the film he loves, and the cynical Valentin listens. Valentin believes in the just cause which makes all suffering bearable; Molina believes in the magic of love which makes all else endurable. Each has always been alone, and always - especially now - in danger of betrayal. But in cell, each surrenders to the other something of himself that he has never surrendered before.